The chaos of collapse : disintegration and reintegration of inter-regional systems - Stone, Tammy
The collapse of organizational systems often results in dramatic re-organization of the social, political, ritual and economic ties that formerly integrated large areas. Such collapse can also result in isolation, and the breakdown of communication and cooperation between communities, and may lead to regional factionalism. This process is examined in the Zuni region of the American Southwest using changes in architecture and ceramics.